2021
DOI: 10.1159/000515060
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Chinese Famine in the Early Life, Adulthood Obesity Patterns, and the Incidence of Hypertension: A 22-Year Cohort Study

Abstract: <b><i>Introduction:</i></b> Little is known regarding the joint associations of famine exposure and obesity patterns with the incidence of hypertension. <b><i>Methods:</i></b> We defined famine exposure cohorts as follows: nonexposure (born between 1962 and 1965), fetal life exposure (born between 1959 and 1961), early childhood exposure (born between 1956 and 1958), midchildhood exposure (born between 1953 and 1955), and late childhood exposure (born between 194… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Previous studies have also shown that exposed to famine in early life is a risk factor for NAFLD. 20 A larger study by Lu 21 showed that women and men exposed to famine had a significantly higher risk of NAFLD than those not exposed. Data from Chongqing city suggest similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that exposed to famine in early life is a risk factor for NAFLD. 20 A larger study by Lu 21 showed that women and men exposed to famine had a significantly higher risk of NAFLD than those not exposed. Data from Chongqing city suggest similar results.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the effect of famine exposure on CVD risk in MS patients has not been evaluated, but studies confirmed that fetal exposure to famine increases CVD risk in those with the component of MS. A cross-sectional study found that the association between early life famine exposure and adult CVD risk appears to be stronger in overweight than in normal individuals [ 26 ]. Other studies showed that fetal exposure to famine exacerbates the adverse effect of hypertension on CVD, especially in individuals with central obesity [ 6 , 27 ]. Zhang et al found that exposure to famine, especially during fetal life, exacerbates the association between hyperglycemia and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Among septal e′ is <8 cm/ s, lateral e′ is <10 cm/s, and LAVI ≥34 mL/m 2 , the presence of 2 abnormal measurements was defined as LVDD. The LVDD grade was defined as (1) grade I: the mitral E/A <0.8, deceleration time >200 ms, the average E/e′ ratio is <8 (septal and lateral); (2) grade II: the mitral E/A ratio is 0.8-1.5 and decreases by ≥50% during the Valsalva maneuver, deceleration time is from 160 to 200 ms, the average E/e′ ratio is 9-12; (3) grade III: the E/A ratio ≥2, deceleration time <160 ms, average E/e′ ratio >13. In this study, the proportion of grade II (13.4%) or III (0.3%) diastolic dysfunction was relatively low.…”
Section: Study Outcomes Evaluationmentioning
confidence: 99%
“…However, the underlying mechanisms that connect these factors are not yet fully understood. Previous studies have revealed famine exposure leads to diseases associated with CVD, such as hypertension [2,3], obesity [2,4], nonalcoholic fatty liver disease [5], diabetes [6,7], and metabolic syndrome [8]. The impact of malnutrition during fetal development and low birth weight on cardiac damage in adolescents is well established [9].…”
Section: Introductionmentioning
confidence: 99%